2010
DOI: 10.1021/op100010n
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Scaleable Process for the Synthesis of a Next-Generation Statin

Abstract: This manuscript details the process research and development of a convergent and safe approach to 1 on a multikilo scale. Specific highlights of the process development efforts will be described, including the development of a dehydrogenation method for dihydropyrimidines and a thermochemically safe synthesis of a 1,2,4-aminotriazole fragment. A key feature of the synthesis is the use and optimization of a modified Julia-Kocienski olefination reaction. Specifically, we report an unprecedented dependence of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 20 publications
0
32
0
Order By: Relevance
“…Therefore, the key process parameters of pH, temperature, and initial substrate and CN -concentration were investigated, to determine their influence on the stability and activity of both of these enzymes when separately expressed in E. coli. These investigations revealed that both Hhe and AtNIT2 were thermally stable up to 30 C and operated best at pH 8.0 (Hhe) and 9.0 (AtNIT2), respectively. Moreover, the inhibitory effects of CN -and 17 on AtNIT2 were quantified.…”
Section: Asn146 His143mentioning
confidence: 96%
See 3 more Smart Citations
“…Therefore, the key process parameters of pH, temperature, and initial substrate and CN -concentration were investigated, to determine their influence on the stability and activity of both of these enzymes when separately expressed in E. coli. These investigations revealed that both Hhe and AtNIT2 were thermally stable up to 30 C and operated best at pH 8.0 (Hhe) and 9.0 (AtNIT2), respectively. Moreover, the inhibitory effects of CN -and 17 on AtNIT2 were quantified.…”
Section: Asn146 His143mentioning
confidence: 96%
“…As a consequence, several new hepatoselective analogs of atorvastatin were derived, such as 1 [22] [29], and 8 [35]. Similarly, more hepatoselective derivatives of rosuvastatin (e.g., derivative 9) have been investigated [28,30]. Quinoline derivatives analogous to pitavastatin (e.g., derivative 10) have also been identified as interesting targets in this context [25,32,36].…”
Section: Hepatoselective Super-statinsmentioning
confidence: 99%
See 2 more Smart Citations
“…This approach provided initial stereoselectivities of 15:1 for E-olefin, which dramatically increased to >100:1 in favor of E-isomer when the reaction mixture was 'aged' after reagents addition at noncryogenic temperatures. 25 Based on the above mentioned shortcomings of other routes to super-statins and our recent success in the first successful assembly of rosuvastatin 26 and pitavastatin 27 via lactonized statin sidechain precursor 1 28 employing the Wittig reaction, we were prompted to consider the assembly of rosuvastatin and pitavastatin via Julia-Kocienski olefination employing lactone 1. This would also enable us to verify, if the suboptimal stereoselectivity of our Wittig approach with lactone 1, where an E/Z ratio between 7:1 and 12:1 was achieved, 26,27 could be improved.…”
mentioning
confidence: 99%